Photovoice as a Participatory Learning Method in Writing - Fauziah Rizqyana Dien Rosmawanty; Tryanti R. Abdulrahman (TRANSBAHASA, 2021)
This study is aimed at examining how EFL students in Indonesia utilized photovoice in writinganalytical exposition text and exploring their experience as well as perception in learning to write. Four (4) students of senior high school in Indonesia who are taken randomly participated in this qualitative study. The data were gathered from students’ writing of analytical text along with the picture/photograph and interview. Students’ photographs and analytical text were analyzed using photovoice analysis procedures. It consisted of selecting, contextualizing, and codifying phases. Results found three main themes: the main idea, generic structure, and language features. According to the results, photovoice is not only effective for students but als makes them feel interested and motivated in learning writing. In addition, photovoice allows students to express their creativity through the lens of a camera. Photovoice has incredibly fostered students’ learning in writing. They all have positive attitudes toward photovoice participatory learning. Thus, it can be a pedagogical tool to teach writing in an EFL setting. Although this study yielded positive outcomes in writing skills, this can not overgeneralize the outcomes. Therefore, future studies on how students write other writing genres in EFL classrooms need to be conducted.